Hubungan Antara Iklim Organisasi Dengan Intensi Turn Over Pada Karyawan Bank - Sari, Mega Arum (2016)
Every established organization cannot avoid conflict, difference in opinions among members, to the personal ambition of both the members and the leaders. It makes the situation in an organization always deals with the phenomenon of turnover. The phenomenon of members' turnover in an organization is often considered as a usual thing, not strange anymore. Many factors trigger the increase in the number of turnover, one of them is organization as the main cause factor. A positive organizational climate can make the employees felt respected and treated by the organization, therefore, they will always keep developing an organization. This research aims at knowing: (1) The correlation between the organizational climate and intension of turn over on the Bank employees; (2). The effective contribution of the organizational climate on the intension of turn over on the Bank employees; (3). The level of the organizational climate and intension of turn over on the Bank employees. Hypothesis proposed is: "There is a negative correlation between the organizational climate and the intension of turnover, in which the better the organizational climate on the employees, the lower the intension of turnover will be. The subject of this research is the employees of Bank Bukopin Syariah of Surakarta branch as many as 42 people. This research used population study that is the researcher used all population or all employees as the subject of research. The tool of data collection used the scale of organizational climate and the scale of turn over intension. The technique of data analysis used the correlation analysis of product moment. The result of data analysis obtained the value of correlation coefficient (r) as much as -0.648 with significance 0.000 (p < 0.01). It means that there is a very significant negative correlation between the organizational climate and the intension of turnover. The better the organizational climate, the lower the intension of turnover will be, so is the opposite, the worse the organizational climate, the higher the intension of turnover will be. The organizational climate has an effective contribution as much as 41.9% on the intension of turnover. The level of the organizational climate of the research subject is categorized as moderate that can be viewed from the empirical mean as much as 90.36. The hypothetic mean is 95. The level of turnover intension of the research subject is categorized as moderate that can be viewed from the empirical mean as much as 123.24 and the hypothetic mean as much as 122.5. Keywords: Intension of Turnover, Organizational Climate.